Simultaneous determination of bicyclol and its two active metabolites concentration in rat plasma and application for pharmacokinetics study of bicyclol and optimized bicyclol-nanoparticles - Xucong Huang; Zhenghua Wu; Yanchao Liu; Mengqi Jia; Wenjuan Zhao; Shuowen Wang; Xinhui Jiang; Yuefen Lou; Guorong Fan (Arabian Journal of Chemistry, 2023)
A simple, sensitive, and rapid LC-MS/MS method for the simultaneous determination of BIC, the M7 and M8 active metabolites in SD rat plasma was developed. After salting-out assisted liquid–liquid extraction (SALLE) with 5 M ammonium acetate solution, the sample was analyzed on a Sciences column (C18 3.0 × 100 mm, 3 μm) using a gradient elution at 40 ℃ within 7 min. The assay displayed excellent linearity in the range of 4–2000 ng/mL for M7 and BIC, and 1–500 ng/mL for M8. The results of this method exhibited that the precision, accuracy, matrix effect, recovery, and stability of BIC, M7 and M8 met all requirements for the quantitation in plasma samples. The pharmacokinetic result showed that the AUC(0→t) was calculated as 383.1 ± 164.4 (ng/mL·h) for BIC, and 5627 ± 1261 (ng/mL·h) for M7 after oral administration with BIC. Compared with BIC group, the pharmacokinetic parameters in BIC-NPs group were improved. Augmentation in AUC(0→t) (3.02-fold) and t1/2 (1.43-fold) for BIC. Meanwhile, double peak phenomenon was observed on the mean plasma concentration–time curves of M7 in BIC and BIC-NPs group. In conclusion, both BIC and BIC-NPs were metabolized to abundant M7 in SD rat, which would provide a basis for researching the treatment mechanism of liver injury.